Use of sonography to evaluate carotid atherosclerosis in the elderly. The Cardiovascular Health Study. CHS Collaborative Research Group. - O'Leary, D H; Polak, J F; Wolfson, S K; Bond, M G; Bommer, W; Sheth, S; Psaty, B M; Sharrett, A R; Manolio, T A (Stroke, 1991)
Carotid sonography is being performed on more than 5,000 participants in the Cardiovascular Health Study, a prospective, multicenter study of cardiovascular disease in men and women aged 65 years and older. The sonographic methods used to examine and measure the extracranial carotid arteries are described. Initial validation studies were performed on 61 subjects with a mean age of 68.6 years. Analysis of within- and between-sonographer differences and between-reader differences were performed for selected variables. In general, the mean absolute differences for within- and between-sonographer comparisons were small, with even less variability between readers. Variability was less for the common carotid artery than for the internal carotid artery. These data suggest that carotid sonography is a reliable and reproducible method for use in the study of carotid atherosclerosis in population studies.
Keywords: Age Factors; Aged; Arteriosclerosis; Carotid Arteries; Carotid Artery Diseases; Carotid Artery, Internal; Female; Humans; Image Interpretation, Computer-Assisted; Image Processing, Computer-Assisted; Male; Prospective Studies; Ultrasonography

Fibrinolytic activation markers predict myocardial infarction in the elderly. The Cardiovascular Health Study. - Cushman, M; Lemaitre, R N; Kuller, L H; Psaty, B M; Macy, E M; Sharrett, A R; Tracy, R P (Arterioscler Thromb Vasc Biol, 1999)
Coagulation factor levels predict arterial thrombosis in epidemiological studies, but studies of older persons are needed. We studied 3 plasma antigenic markers of fibrinolysis, viz, plasminogen activator inhibitor-1 (PAI-1), fibrin fragment D-dimer, and plasmin-antiplasmin complex (PAP) for the prediction of arterial thrombosis in healthy elderly persons over age 65. The study was a nested case-control study in the Cardiovascular Health Study cohort of 5201 men and women >/=65 years of age who were enrolled from 1989 to 1990. Cases were 146 participants without baseline clinical vascular disease who developed myocardial infarction, angina, or coronary death during a follow-up of 2.4 years. Controls remained free of cardiovascular events and were matched 1:1 to cases with respect to sex, duration of follow-up, and baseline subclinical vascular disease status. With increasing quartile of D-dimer and PAP levels but not of PAI-1, there was an independent increased risk of myocardial infarction or coronary death, but not of angina. The relative risk for D-dimer above versus below the median value (>/=120 microg/L) was 2.5 (95% confidence interval, 1.1 to 5.9) and for PAP above the median (>/=5.25 nmol/L), 3.1 (1.3 to 7.7). Risks were independent of C-reactive protein and fibrinogen concentrations. There were no differences in risk by sex or presence of baseline subclinical disease. D-dimer and PAP, but not PAI-1, predicted future myocardial infarction in men and women over age 65. Relationships were independent of other risk factors, including inflammation markers. Results indicate a major role for these markers in identifying a high risk of arterial disease in this age group.
Keywords: Age Factors; Aged; Angina Pectoris; Biomarkers; Female; Fibrin Fibrinogen Degradation Products; Fibrinolysin; Fibrinolysis; Follow-Up Studies; Heart Arrest; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Risk Factors

Retinal microvascular abnormalities and blood pressure in older people: the Cardiovascular Health Study. - Wong, T Y; Hubbard, L D; Klein, R; Marino, E K; Kronmal, R; Sharrett, A R; Siscovick, D S; Burke, G; Tielsch, J M (Br J Ophthalmol, 2002)
AIM: To examine the relation between blood pressure and retinal microvascular abnormalities in older people. METHODS: The Cardiovascular Health Study is a prospective cohort study conducted in four US communities initiated in 1989 to 1990. Blood pressure was measured according to standardised protocols at each examination. During the 1997-8 examination, retinal photographs were taken of 2405 people aged 69-97 years (2056 without diabetes and 349 with diabetes). Signs of focal microvascular abnormalities (focal arteriolar narrowing, arteriovenous nicking, and retinopathy) were evaluated from photographs according to standardised methods. To quantify generalised arteriolar narrowing, the photographs were digitised and diameters of individual arterioles were measured and summarised. RESULTS: In non-diabetic people, elevated concurrent blood pressure taken at the time of retinal photography was strongly associated with presence of all retinal microvascular lesions. The multivariable adjusted odds ratios, comparing the highest to lowest quintile of concurrent systolic blood pressure, were 4.0 (95% confidence intervals (CI): 2.4 to 6.9, p test of trend<0.001) for focal arteriolar narrowing, 2.9 (95% CI: 1.6 to 5.3, p<0.001) for arteriovenous nicking, 2.8 (95% CI: 1.5 to 5.2, p<0.001) for retinopathy, and 2.1 (95% CI: 1.4 to 3.1, p<0.001) for generalised arteriolar narrowing. Generalised arteriolar narrowing and possibly arteriovenous nicking were also significantly associated with past blood pressure measured up to 8 years before retinal photography, even after adjustment for concurrent blood pressure. These associations were somewhat weaker in people with diabetes. CONCLUSIONS: Retinal microvascular abnormalities are related to elevated concurrent blood pressure in older people. Additionally, generalised retinal arteriolar narrowing and possibly arteriovenous nicking are related to previously elevated blood pressure, independent of concurrent blood pressure. These data suggest that retinal microvascular changes reflect severity and duration of hypertension.
Keywords: Aged; Aged, 80 and over; Blood Pressure; Cohort Studies; Diabetic Retinopathy; Eye; Female; Humans; Male; Microcirculation; Prospective Studies; Retina; Retinal Diseases

Lack of association of the plasminogen activator inhibitor-1 4G/5G promoter polymorphism with cardiovascular disease in the elderly. - Crainich, P; Jenny, N S; Tang, Z; Arnold, A M; Kuller, L H; Manolio, T; Sharrett, A R; Tracy, R P (J Thromb Haemost, 2003)
Elevated circulating plasminogen activator inhibitor-1 (PAI-1) may increase risk of cardiovascular disease (CVD). The 4G allele of the 4G/5G PAI-1 promoter polymorphism is associated with higher levels of PAI-1. We examined the association of PAI-1 4G/5G genotype and CVD events in the elderly participants of the Cardiovascular Health Study (CHS). We measured 4G/5G genotype in a nested case-control study within the CHS. Cases included incident angina, myocardial infarction (MI), and stroke. 4G/5G genotype was not found to be associated with markers of fibrinolysis or CVD risk in the selected elderly cohort. There were no differences in genotype frequencies by case-control status (5G/5G frequency 16-22%; chi2P= 0.07). The 5G allele was not associated with incident CVD events when individuals with at least one 5G allele were compared to 4G/4G homozygotes. The presence of at least one 4G allele was likewise not associated with incident CVD when those with 4G/4G and 4G/5G genotypes were compared to 5G/5G homozygotes. Our results suggest that the PAI-1 4G/5G promoter polymorphism is not associated CVD risk factors or incident CVD events in the elderly.
Keywords: African Continental Ancestry Group; Aged; Alleles; Cardiovascular Diseases; Case-Control Studies; Cohort Studies; European Continental Ancestry Group; Female; Genotype; Homozygote; Humans; Male; Myocardial Infarction; Plasminogen Activator Inhibitor 1; Polymorphism, Genetic; Promoter Regions, Genetic; Risk

Soluble intracellular adhesion molecule-1 is associated with cardiovascular disease risk and mortality in older adults. - Jenny, N S; Arnold, A M; Kuller, L H; Sharrett, A R; Fried, L P; Psaty, B M; Tracy, R P (J Thromb Haemost, 2006)
BACKGROUND: Intracellular adhesion molecule-1 (ICAM-1) regulates leukocyte-endothelial attachment, a process crucial to atherosclerosis. Circulating soluble ICAM-1 (sICAM-1) may serve as a marker of cardiovascular disease (CVD) progression. OBJECTIVES: We examined the association of sICAM-1 with measures of subclinical CVD and risk of incident CVD events and death in older men and women (age > or = 65 years) from the Cardiovascular Health Study. METHODS: Selected participants were free of clinical CVD at baseline. Non-exclusive incident case groups were angina (n = 534), myocardial infarction (n = 304), stroke (n = 327), and death (n = 842; CVD death = 310). A total 643 subjects were free of events during follow-up. RESULTS: sICAM-1 was positively associated with C-reactive protein, interleukin-6 and fibrinogen and measures of subclinical CVD in these older men and women. In Cox regression models adjusted for age, gender, and race, increasing levels of sICAM-1 were associated with increased risk of all cause mortality in men and women. Hazard ratios (95% confidence intervals) for a one standard deviation increase in sICAM-1 (89.7 ng mL(-1)) were 1.3 (1.1-1.4) in men and 1.2 (1.1-1.3) in women. sICAM-1 was associated with increased risk of CVD death in women (1.2; 1.0-1.5), but not men (1.1; 0.9-1.3). There were no associations of sICAM-1 with non-fatal CVD events. CONCLUSIONS: While sICAM-1 was associated with death in older men and women, there was a more marked association between sICAM-1 and CVD death in women.
Keywords: Aged; Aged, 80 and over; Angina Pectoris; Biomarkers; Cardiovascular Diseases; Female; Humans; Incidence; Intercellular Adhesion Molecule-1; Male; Mortality; Myocardial Infarction; Regression Analysis; Risk Factors; Sex Factors; Solubility; Stroke